Einblicke in die Kinderstube der Ribosomen - Baßler, Jochen; Hurt, Ed (Biospektrum, 2015)
Ribosome formation can be imagined like an assembly line for automobile production. Pre-ribosomes transit through a number of ‘mounting-stages’. These different steps are catalyzed by about 200 assembly factors that bind transiently to the evolving ribosome. However, it currently remains unclear how this myriad of factors can trigger ribosome synthesis. Insight into the mechanism of ribosome biogenesis also has medical relevance, since there are diseases in which ribosome assembly is disturbed.
Gesehen am 03.08.2020